Organizational Aspects of Managing the Robotic Process Automation (RPA) Department: The Example of a Polish SAP Service Provider - Katarzyna Jasinska (Communications of International Proceedings, 2024)
The technological development of enterprises is one of the key challenges faced by modern entities. Enterprises are looking for more and more easily adoptable low-code technologies, an example of which is RPA. The success of implementations depends to a large extent on the professional competences and knowledge of entities implementing RPA projects. The literature on the subject contains many studies on the RPA technology itself or its applications in enterprises. However, there are few studies on the management of organizations focused on implementing RPA projects. The article fills this gap. The aim of the article is to analyze and evaluate the management of the RPA department on the example of a company providing SAP and RPA services. The article uses literature analysis and a case study of a company providing SAP and RPA services operating on the Polish market as a research method. One of the key conclusions from the conducted research was that there is little complexity in the integration of the use elements of the 7S model in the RPA department,and the implementation of soft elements of the 7S model is important to create market advantage. Surprisingly difficulties were identified in adapting the hard elements of the model to the requirements of the parent company, related to poor understanding of the characteristics of the RPA team's operation in the post-transactional integration process.
Keywords: RPA; 7S model; management